ANALISIS PROSES REKRUTMEN DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. SUPRA BOGA LESTARI, TBK. JAKARTA BARAT - Mawarni, Widya; Sularmi, Lili (Journal of Research and Publication Innovation, 2024)
This research aims to analyze and describe the employee recruitment process at PT. Supra Boga Lestari, Tbk. West Jakarta. This research is a qualitative research. Data collection uses interview techniques with one of the employees (as a resource person) who works at PT. Supra Boga Lestari, Tbk. "Ranch Market" West Jakarta, then analysis techniques using the Miles and Huberman technique, namely data reduction, data presentation and data verification. The research results show that the recruitment process at PT. Supra Boga Lestari, Tbk. West Jakarta, includes several stages, namely: analyzing the company's position requirements, posting job vacancy news in various media, and processing job applications that have been submitted by prospective employees. The recruitment process aims to improve employee performance at PT. Supra Boga Lestari, Tbk. West Jakarta. In order to maintain excellent service (service excellence), Ranch Market always provides a pleasant shopping experience, which customers can feel every time they shop.